The wonder of you [large type] : a Christiansen Family novel - Warren, Susan May, 1966- (Warren, Susan May, 1966- Christiansen family novel., 2015)
"Mortified after her semester abroad is cut short, Amelia Christiansen returns to Deep Haven, certain she isn't brave enough for the adventures she's dreamed of. The last thing she expects is for the man who broke her heart to cross the Atlantic and beg forgiveness"--